“Desarrollo de una app móvil para la comunicación interna de la Universidad Técnica de Cotopaxi: Módulo docentes y servidores” - Bustamante Flores, Graciana Alexandra (2024)
Communication has always been a fundamental pillar for the formation and development of society. In this increasingly globalized world, it has had to evolve to adapt to new needs and face the digital era. The Technical University of Cotopaxi, an institution recognized for its commitment to quality education and the academic growth of the region, has not been immune to these challenges. Despite its prestige, it has been affected by significant internal communication problems that affect the proper work performance of its faculty and staff, limiting the efficiency of academic and administrative management. To address this problem and improve the information flow of the university community, the development of a mobile application to optimize internal communication has been proposed. This project contemplates the creation of specific modules for faculty and staff, which are designed to meet the needs of these groups within the institution. The proposal is based on a significant literature review that has served as a guide to gathering relevant information to corroborate the development of this application and the feasibility it could have in an institutional environment with the help of tools such as the React Native framework, React, SQL Server and Visual Studio Code. The project provides users with functionalities such as immediate access to important institutional news and events, as well as real-time notifications of the institution's activities. These functionalities ensure that both faculty and staff remain continuously informed, thus contributing to a more productive and connected academic environment.